Evaluation and Treatment of Posterior Tibialis Tendon Insufficiency in the Elderly Patients. (22nd January 2019) - Ikpeze, Tochukwu C.; Brodell, James D.; Chen, Raymond E.; Oh, Irvin
Introduction: Posterior tibialis tendon insufficiency is the most common cause of adult acquired flatfoot deformity in elderly patients. We performed a literature search of primary and secondary journal articles pertaining to posterior tibialis tendon insufficiency in the geriatric population. We examined relevant data from these articles regarding current evaluation in addition to both conservative and advanced treatment approaches that correspond to disease severity. Significance: There is a paucity of literature to guide treatment of posterior tibialis tendon insufficiency in the elderly, and this condition may be more prevalent in geriatric patients than previously realized. Results: Posterior tibialis tendon insufficiency is an acquired defect that affects 10% of the geriatric population and disproportionately affects women. It is typically caused by degenerative changes. There are four primary stages of posterior tibialis tendon with subcategorizations that range from mild to severe. Conservative treatment with a variety of available ankle braces and non-steroidal anti-inflammatory medications are typically used to treat the first and second stage disease. Surgical repair is warranted for advanced second stage and above posterior tendon insufficiency. A variety of techniques have been proposed, and can include tendon transfer, hindfoot fusion, and even total ankle arthroplasty in extreme cases. Conclusion: Posterior tibialis tendon insufficiency causes marked discomfort and alters normal gait biomechanics. Elderly patients typically present with more severe manifestations of the disease. For patients requiring surgery, and especially geriatric patients, the ideal treatment is thought to be a procedure that is minimally invasive in order to maximize positive outcomes for elderly patients. More work is needed to examine clinical and radiographic outcomes of geriatric patients treated for posterior tibialis tendon insufficiency.